(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article explores the key role of guided bone regeneration (GRC) in the context of implantology. GRK presents an innovative method that combines biological principles and surgical precision to overcome the limitations associated with a lack of bone structure. Guided bone regeneration (NCR) in implantology is a modern technique used to restore bone tissue that has formed during inflammation, injury, or after tooth extraction. In implantology, NCR is used to create favorable conditions for the installation of dental implants, especially in cases where the volume of bone tissue is insufficient to fully accommodate the implant. The technique of directed bone regeneration is based on the use of special barrier membranes that create a "cellular barrier structure", causing osteogenic cells (cells capable of forming bone tissue) to migrate to the defect area. The barrier membrane causes other types of cells (for example, epithelial cells) to enter the regeneration zone, which contributes to a better and more accurate restoration of bone tissue. The main stages of targeted bone regeneration: 1. **Defect assessment**: Before performing the NCR, it is necessary to conduct a final examination (for example, using radiography or CT) in order to accurately assess the degree of bone damage and its features.